(untitled) (International Journal of Engineering and Computer Science, 2014)
Ontology is a most essential technology in Data and Knowledge Engineering. Because of Ontology provide many advantages over Object Oriented Concepts, like Knowledge Sharing, reusability, Interoperability and Knowledge Level Validation and Verification. Ontology is a collection of concepts that represent knowledge in the domain and there exist common terminology to provide types, methods and relationship between those concepts in the domain. Ontology used in the form of structural framework in many field like Artificial Intelligence, Information Science, Semantic Web and etc., this concept identification presents an ontology building through the automatic and semi-automatic process. Most of the ontology learning technique developed using the Classifiers, NLP, probabilistic and statistical learning. For the concept identification it uses the process of statistical learning with the combination of text.